Fractured orbital wall reconstruction with an auricular cartilage graft or absorbable polyacid copolymer - Kruschewsky, Leonardo De Souza; Novais, Tatiana; Daltro, Carla; Castelo Branco, Bruno; Lessa, Marcus; Kruschewsky, Marinella Benez; De Mello-Filho, Francisco Verissimo (Wolters Kluwer, 2011)
Objective: The objective of the study was to compare the functional and aesthetic results of fractured orbital wall reconstruction with an auricular cartilage graft or absorbable polyacid copolymer. Materials and Methods: Twenty patients with blow-out orbital fracture/orbital floor associated or not with the medial wall were assessed by the same craniofacial surgical group. All were evaluated preoperatively and postoperatively by an ophthalmologist for diplopia, enophthalmos, exophthalmos, sensitivity, ophthalmic reflexes, intraocular pressure, and visual field.The patients were subjected to a preoperative facial multislice computed tomographic scan, repeated 6 months after surgery. Eight patients underwent reconstruction with an auricular cartilage graft, and 12 patients, with blade absorbable polyacid copolymer. Subtarsal access was used for all patients. Results: Two patients showed temporary ectropion, 1 in each group. All patients presented satisfactory ocular function, and all tests revealed good orbital delineation, orbital symmetry, periorbital sinus individualization, and reduction of blow-out. Conclusions: The blow-out orbital wall reconstruction can be performed with the use of an auricular cartilage or with a blade absorbable copolymer without differences regarding functional or aesthetic complications and sequelae. © 2011 by Mutaz B. Habal, MD.
Keywords: absorbable copolymer; cartilage graft; Orbital fracture; orbital reconstruction; orbital trauma